Usulan Perbaikan Untuk Perusahaan Fashion Berdasarkan Model Niat Beli - Jonathan, Ryanto; Sitompul, Carles (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
X is a bridal company. For the last three years, the income from party dress rental have decreased. The company suspects this is caused by the emergence of new competitors. The company has tried to make improvements. However, these improvements have no effect. Therefore, further research is needed to determine the factors that influenced purchase intention. The research model that’s been used conduct five variable. There are 113 data collected using questionaire. The data will be processed using smart-PLS 30-days trial software and use PLS-SEM method. The test results indicate that there are three variables that affect purchase intention. That variable is social network marketing, consumer engagement, and price consciousness. To make improvement, we used IPMA matrix to determine importance and performance level of each variable. The final result from the research is there are seven proposed improvement that has been accepted by the company.